2016
DOI: 10.1097/aln.0000000000001070
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Catechol-O-methyltransferase–dependent Pain Is Initiated by Peripheral β-Adrenergic Receptors

Abstract: Background Patients with chronic pain disorders exhibit increased levels of catecholamines alongside diminished activity of catechol-O-methyltransferase (COMT), an enzyme that metabolizes catecholamines. The authors found that acute pharmacologic inhibition of COMT in rodents produces hypersensitivity to mechanical and thermal stimuli via β-adrenergic receptor (βAR) activation. The contribution of distinct βAR populations to the development of persistent pain linked to abnormalities in catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 122 publications
2
32
0
8
Order By: Relevance
“…In several studies, postsurgical cancer patients who were met-allele homozygotes had a lower pain threshold and higher levels of fatigue [41]. Consistent with these profiles, in wild-type mice, sustained delivery of the COMT inhibitor OR486 increased sensitivity to mechanically induced pain [63]. COMT knockout mice have enhanced sensitivity to thermal pain, and transgenic mice that overexpress COMT are more resistant to thermal pain [60].…”
Section: Pain and Fatiguementioning
confidence: 81%
“…In several studies, postsurgical cancer patients who were met-allele homozygotes had a lower pain threshold and higher levels of fatigue [41]. Consistent with these profiles, in wild-type mice, sustained delivery of the COMT inhibitor OR486 increased sensitivity to mechanically induced pain [63]. COMT knockout mice have enhanced sensitivity to thermal pain, and transgenic mice that overexpress COMT are more resistant to thermal pain [60].…”
Section: Pain and Fatiguementioning
confidence: 81%
“…Another recent study by our group shows that adrenalectomized rats, lacking peripheral epinephrine, fail to develop increased mechanical and thermal pain sensitivity following sustained COMT inhibition, thus providing further evidence for a peripheral contribution of adrenergic systems to COMT-dependent pain. [10]. Additional work is required to determine the relative contributions of peripheral, spinal, and supraspinal β 2 - and β 3 ARs to COMT-dependent pain.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between inotropic support and disuse of fentanyl in this study was low ( r = 0.16). An experimental animal study revealed that a higher blood catecholamine concentration is associated with increased pain sensitivity via the activation of β-adrenergic receptors in the peripheral sensory nerves [ 18 ].…”
Section: Resultsmentioning
confidence: 99%